A review of the centralized sewerage system for Kuching City - Christina, Umpi. (Universiti Malaysia Sarawak (UNIMAS), 2012)
The centralized sewerage system for Kuching City curently under construction and this project is expected to be completed by october 2012. This system shall collect all the wastewater through sewer network to a centralized treatment plant and using yhe activated sludge system to treat the wastewater. The effluent after being discharged into a constructed wetland before finally flowing into Sarawak River is believed to comply with a Standard A of the enviroment Quality Act requirement. Prior to this, Sarawak river and its tributaries within the study area are polluted. The main source of the pollution is raw and insufficiently treated sewage and wastewater, which is eventually drained to Sarawak River.